A National Mobile Medical Unit (MMU) Program to Address the Healthcare Needs of Veterans Experiencing Homelessness: An Evaluation Protocol - Jillian J Weber; Rebecca L Kinney; Jill S Roncarati; Kenneth Bruemmer; Monica Diaz; Jill Albanese (Health Services Insights)
Background: Homelessness remains a public health concern in the United States (U.S.) and ending veteran homelessness has been a significant priority for the U.S. Department of Veterans Affairs (VA) for over a decade. However, veterans experiencing homelessness (VEH) have unmet healthcare needs and face numerous barriers to accessing and engaging in healthcare. Objectives: The Veterans Health Administration’s (VHA) Homeless Programs Office (HPO) implemented mobile medical units (MMUs) within the tailored primary care model established in 2011 called the Homeless Patient Aligned Care Team (HPACT) program to expand access to care for hard-to-reach VEH. This article outlines the evaluation protocol for the HPACT MMU program to examine the impact of MMUs on engaging and retaining homeless veterans in VA primary care and other supportive services. Design: Using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, we will assess how mobile services engage VEH in VA primary care and preventive care. This 4-year program evaluation includes a plan to collect individual and organizational level quantitative and qualitative data. Discussion: The first stages of program adoption and implementation have been completed resulting in 25 MMUs being deployed across the U.S. that are fully operational and ready to serve VEH. Early outcomes demonstrate the significant impact of the ability MMUs in reducing barriers such as transportation for VEH, while increasing positive veteran health outcomes. Conclusion: This evaluation will provide insight on the innovative ways in which mobile medical units (MMUs) may expand the boundaries of the VA and external health care systems in efforts to improve health equity and access among our most vulnerable populations. Preliminary outcomes show significant engagement with VEH in the community and interest in the model of care. The program has the potential to play an essential role in achieving VA’s goal of ending veteran homelessness.